Effect of Zn additions on the electrochemical migration behaviour of SAC305 solder alloys / Loh Hwei Ling - Loh, Hwei Ling (2019)
The inclusion of lead within the European Union’s Restriction of Hazardous Substances list has led to a push within the microelectronics industry for a suitable non-lead solder alloy substitute with comparable mechanical and chemical properties. Tin-silver-copper (Sn-Ag-Cu) alloys with the addition of zinc (Zn) offers comparable performance in terms of mechanical properties but was found to be lacking in terms of corrosion resistance. In this study, the effect of zinc addition on one aspect of corrosion i.e. electrochemical migration was investigated in 1 wt% of sodium chloride solution with SAC305 as a substrate. The electrochemical migration behavior of these alloys was studied through a water drop test to observe the time-to-failure of the circuit and the subsequent test products studied under scanning electron microscopy (SEM). The water drop test results indicated that the addition of Zn would increase the time-to-failure due to the formation of intermetallic compounds at the surface of the substrate. The addition of Zn also changed the SAC305 dendritic morphology from a fern-like, thick, angular shape to a thinner, more needle-like structure.